METHODS OF CALCULATING THE DYNAMICS OF SLUDGE SEDIMENTS IN WATER DELIVERY CHANNELS OF PUMPING STATIONS (American Journal of Pedagogical and Educational Research, 2024)
In this article, the fractional composition of turbidity and the dynamics of turbid sediments in the channel that brings water to the 1st pumping station of the Karshi main channel are studied.